2017
DOI: 10.1111/echo.13574
|View full text |Cite
|
Sign up to set email alerts
|

Big thrombus “sitting” in an atrial septal aneurysm

Abstract: A 79 year-old-man presented three episodes of upper gastrointestinal bleeding and weight loss. Endoscopy revealed bleeding and extrinsic compression at the pyloric region. Computed tomography scan showed a pancreatic tumor, peritoneal carcinomatosis, vascular infiltration, and incidentally found a partially calcified hypodense lesion of 35 mm in the left atrium, suggesting a myxoma or a thrombus. Echocardiography revealed moderate left atrium enlargement, dilated left atrial appendage with spontaneous echo con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…Atrial thrombi masquerading as myxomas have been reported in the literature, with echocardiography and cardiac magnetic resonance being among the diagnostic modalities used. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 We conducted a PubMed search for reports of left atrial thrombi misdiagnosed as myxomas and found 24 cases, 20 of which had predisposing procoagulant conditions, namely, atrial fibrillation in 11 patients, mitral stenosis in five patients, left ventricular dysfunction in three patients, and systemic lupus erythematosus in one patient. Details were not available for three patients, and one patient had undergone cardiac transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial thrombi masquerading as myxomas have been reported in the literature, with echocardiography and cardiac magnetic resonance being among the diagnostic modalities used. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 We conducted a PubMed search for reports of left atrial thrombi misdiagnosed as myxomas and found 24 cases, 20 of which had predisposing procoagulant conditions, namely, atrial fibrillation in 11 patients, mitral stenosis in five patients, left ventricular dysfunction in three patients, and systemic lupus erythematosus in one patient. Details were not available for three patients, and one patient had undergone cardiac transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Details were not available for three patients, and one patient had undergone cardiac transplantation. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45…”
Section: Discussionmentioning
confidence: 99%
“…Из 15 подходящих под критерии публикаций были отобраны только клинические случаи АМПП без сопутствующих шунтов (открытого овального окна и/ или дефекта МПП) (табл.). Из 8 опубликованных клинических случаев лишь в трех у пациентов напрямую были визуализированы тромботические массы в АМПП [4][5][6], причем в двух из них у пациентов были верифицированы эмболические очаги в головном мозге [4,5], еще один случай [6] не подходил под вышеупомянутые критерии, потому что эмболических событий у пациента на момент обследования выявлено не было, а тромб в АМПП был ассоциирован с онкологическим заболеванием (опухоль поджелудочной железы).…”
Section: Discussionunclassified
“…There are different theories which try to explain increased thromboembolism in patients with ASA. 42 The ASA can be a direct source of thrombus formation. 42 There are reports documenting thrombotic material within the aneurysmal sac in patients at autopsy or cardiac surgery and micro thrombi attached to or generated within the cul de sac of the ASA.…”
Section: Atrial Septal Aneurysm: Clinical Presentationsmentioning
confidence: 99%
“…42 The ASA can be a direct source of thrombus formation. 42 There are reports documenting thrombotic material within the aneurysmal sac in patients at autopsy or cardiac surgery and micro thrombi attached to or generated within the cul de sac of the ASA. 43 It has also been noted that there are marked thickening of the atrial septum suggestive of thrombus formation in patients with ASA.…”
Section: Atrial Septal Aneurysm: Clinical Presentationsmentioning
confidence: 99%